2008
DOI: 10.1093/jn/138.6.1192s
|View full text |Cite
|
Sign up to set email alerts
|

Health Claim Evidence Requirements in Japan

Abstract: In the early 1980s the Japanese scientific academy defined a functional food as a food having a tertiary or physiologically active function. The current Japanese "Food with Health Claims" include 2 categories. For the first category, "Food with Nutrient Function Claims," the label may be freely used if a product satisfies the standard for the minimum and maximum levels per daily portion usually consumed. The second category is defined as "Food for Specified Health Uses" (FOSHU). FOSHU foods are those that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
83
1
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 13 publications
0
83
1
13
Order By: Relevance
“…It has been reported that catechins reduce body fat and weight (12)(13)(14)(15). On the basis of these reports, green tea beverages containing catechins, such as EGCG, were approved as Food for Specified Health Uses (FOSHU) (16) by the Consumer Affairs Agency of Japan, and were recommended for reducing body fat. As a result, people who drink these beverages in large quantities will be ingesting catechins in amounts never ingested before.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that catechins reduce body fat and weight (12)(13)(14)(15). On the basis of these reports, green tea beverages containing catechins, such as EGCG, were approved as Food for Specified Health Uses (FOSHU) (16) by the Consumer Affairs Agency of Japan, and were recommended for reducing body fat. As a result, people who drink these beverages in large quantities will be ingesting catechins in amounts never ingested before.…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese government regulates supplements and functional foods in two categories ( 3 ). One is Food for Specified Health Uses (FOSHU), and the other is Food with Nutrient Function Claims (FNFC), which contains vitamins and minerals that have accumulating scientific evidence for their safety and efficacy as in the Dietary Reference Intakes ( 4 ), and corresponds to dietary supplements in the United States.…”
mentioning
confidence: 99%
“…Enacted in 1991, Japan's regulations under Food for Specified Health Uses (FOSHU) is considered among the most advanced, with eight categories of health claims (18) . As of 2007, 755 items had been approved for FOSHU status (18) (19) and the European Commission has authorised the use of seven disease reduction health claims (20) . In the USA, the Food and Drug Administration (FDA) has authorised twelve health claims under the Nutrition Education Labeling Act (NELA).…”
Section: Regulatorsmentioning
confidence: 99%